2020
DOI: 10.37689/acta-ape/2020ao0023
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação dos efeitos da educação permanente para enfermagem em uma organização hospitalar

Abstract: Avaliação dos efeitos da educação permanente para enfermagem em uma organização hospitalar Assessment of continuing education effects for nursing in a hospital organization Evaluación de los efectos de la educación permanente para enfermeros en una organización hospitalaria

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
1
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 14 publications
1
1
0
4
Order By: Relevance
“…18 It is of great importance to implement continuing education to update the health teams, since being in working spaces contributes to greater safety in care and improves the knowledge of professionals, favoring professional satisfaction and quality care. 19 Regarding the specific aspects, the data from this study are similar to those found in the literature about the detection of cardiac arrest, since 66.67% of the nurses answered partially correctly about the identification of cardiac arrest. 20 Considering that it is the first step to initiate cardiopulmonary resuscitation maneuvers in BLS, it is necessary to provide fast, accurate, and systematized care to this user.…”
Section: Discussionsupporting
confidence: 81%
“…18 It is of great importance to implement continuing education to update the health teams, since being in working spaces contributes to greater safety in care and improves the knowledge of professionals, favoring professional satisfaction and quality care. 19 Regarding the specific aspects, the data from this study are similar to those found in the literature about the detection of cardiac arrest, since 66.67% of the nurses answered partially correctly about the identification of cardiac arrest. 20 Considering that it is the first step to initiate cardiopulmonary resuscitation maneuvers in BLS, it is necessary to provide fast, accurate, and systematized care to this user.…”
Section: Discussionsupporting
confidence: 81%
“…A prática educativa hospitalar se faz necessário de forma permanente nos ambientes hospitalares públicos e privados, julgando-se primordial a capacitação de todos os profissionais de saúde que prestam assistência diretamente aos clientes, para minimizar quaisquer tipos de agravamento a saúde e erros (Sade et.;. A educação corporativa é muito importante para as resolutividades necessárias a serem abordadas nos treinamentos, melhorando a performance dos profissionais, cujo que é preciso a todo momento ter esse ambiente de capacitação e reciclagem dos trabalhadores.…”
Section: Resultsunclassified
“…Com isso Sade et al, (2020) mostra que 60% dos ambientes de trabalho em saúde são compostos pela enfermagem, com um conjunto de educação continuada é possível relacionar aos efeitos positivos na transformação das práticas laborais.…”
Section: Discussionunclassified